A co-designed telehealth-based model of care to improve attendance and completion to cardiac rehabilitation of rural and remote Australians: The Country Heart Attack Prevention (CHAP) project. (December 2021) - Beleigoli, Alline; Champion, Stephanie; Tirimacco, Rosy; Nesbitt, Katie; Tideman, Philip; Clark, Robyn A
We aim to report the co-design of the implementation strategy of a telehealth-enabled cardiac rehabilitation model of care in rural and remote areas of Australia. The goal of this model of care is to increase cardiac rehabilitation attendance and completion by country patients with cardiovascular diseases. We hypothesise that a model of care co-designed with stakeholders will address patients' needs and preferences and increase participation. We applied the Model for Large Scale Knowledge Translation and engaged with patients, clinicians and health service managers across six local health networks in rural South Australia. They informed the design of a web-based cardiac rehabilitation programme and the delivery of the expanded telehealth service. The stakeholders defined face-to-face, telephone, web-based or combinations as choices of mode of delivery to patients referred to cardiac rehabilitation. A case-managed programme supported by a web portal with an interface for patients and clinicians was considered more appropriate to the local context than a self-managed programme. A business model was developed to enable the sustainability of cardiac rehabilitation clinical assessments through primary care. The impact of the model of care on cardiac rehabilitation attendance/completion, clinical outcomes, patient-reported outcomes and patient-reported experiences and cost-effectiveness will be tested in a 12-month follow-up study.